2023
DOI: 10.1097/qco.0000000000000967
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus in children: epidemiology and clinical impact post-COVID-19

Emily Rice,
Daniel B. Oakes,
Charlie Holland
et al.

Abstract: Purpose of review Respiratory syncytial virus (RSV) remains a leading cause of mortality and morbidity worldwide. RSV seasonality was disrupted by COVID-19-associated nonpharmaceutical interventions (NPIs). We review RSV seasonality, molecular epidemiology, clinical manifestations, and community awareness to inform future prevention strategies. Recent findings An initial reduction of RSV disease observed with NPIs, and subsequent global resurgence was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In the first 2 years of the pandemic, a new subtype shift was observed and RSV‐B became dominant. In the last season (2022–2023), epidemiological control measures were relaxed and both subtypes were observed to circulate in the same proportions Post‐COVID‐19 resurgence was reported with both RSV subtypes and countries such as Italy observed approximately equal subtype cocirculation 32 In a study carried out in Sicily, a similar proportion was also found in the season 2022–2023, but it is common in this area since it also occurred in 2017–2018 and 2021–2022 33…”
Section: Discussionmentioning
confidence: 94%
“…In the first 2 years of the pandemic, a new subtype shift was observed and RSV‐B became dominant. In the last season (2022–2023), epidemiological control measures were relaxed and both subtypes were observed to circulate in the same proportions Post‐COVID‐19 resurgence was reported with both RSV subtypes and countries such as Italy observed approximately equal subtype cocirculation 32 In a study carried out in Sicily, a similar proportion was also found in the season 2022–2023, but it is common in this area since it also occurred in 2017–2018 and 2021–2022 33…”
Section: Discussionmentioning
confidence: 94%
“… 18 24 Other researchers also indicated that the median age of children admitted for RSV infection increased during the resurgence of the virus during the postpandemic period. 25 26 In the present study, most viruses, including nonenveloped viruses (HRV, AdV, and HBoV), as well as RSV, exhibited a significant increase in the mean age of patients during the postpandemic years compared with the prepandemic years. One possible explanation is that more severe infections might have occurred in older children after the COVID-19 pandemic due to the reduced natural immunity to the corresponding viruses and the increased virus coinfection rate.…”
Section: Discussionmentioning
confidence: 46%
“…In addition, it is possible that respiratory viral testing capacity and behavior has increased because COVID-19 has raised global community concern and awareness about respiratory infections. 25 Viral testing could have increased for older children after the pandemic compared with before. However, the age distribution of patients with IFV during the postpandemic years is unique.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have observed that in the post-lockdown period, especially patients with bocavirus and RSV-related infections more frequently required intensive care and had a more severe disease course compared to other seasonal respiratory virus infections. Rice et al drew attention to the increase in the incidence rates of RSV infections during the post-pandemic period [24]. Boggio et al and Karbuz et al highlighted the higher rates of bocavirus infections, the need for intensive care and the severe course of the disease in the post-pandemic period [15,25].…”
Section: Discussionmentioning
confidence: 99%